Hospital Criminal Liability for Patient's Damages due to Health Service Errors during the Covid-19 Pandemic - Diana Yusyanti (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
During the Covid-19 pandemic, many mass media reported various cases of health service errors at hospitals that resulted in material losses, there were even cases of patients dying. The criminal aspect is explicitly stated in the provisions of Article 190 of Law No. 36 Year 2009 and Article 62 and Article 63 of Law No. 44 Year 2009 and Article 46 of Law Number 44 Year 2009 concerning Hospitals where it is stated that hospitals are legally responsible for all losses due to negligence or health service errors. This research used descriptive normative research through a statutory approach, carried out by reviewing all laws related to legal issues that are being handled. In addition, criminal sanctions in Law Number 36 Year 2009 are formulated cumulatively, such as in the case of criminal acts as referred to in Article 190 paragraph (1), Article 191, Article 192, Article 196, Article 197,Article 198, Article 199, and Article 200, accumulated so that the general provisions inArticle 30 of the Criminal Code are ineffective, that the maximum sanction if not paid the perpetrators are only subject to a substitute imprisonment of 6 months or 8 months.